Fenomena Faktor yang Mempengaruhi Nilai Perusahaan - Damayanthi, I Gusti Ayu Eka (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019), 2019)
This study explains the phenomenon of factors that influence company value. Based on the phenomenon and associated with the theory, the factors that influence company value are social responsibility disclosure (CSR), good corporate governance (GCG) and foreign ownership (KA). The success of a company is often associated with stock prices and company value. The stock prices for companies that have good value tend to be high both short and long term. The research objective is to provide empirical evidence that CSR disclosure factors, GCG and KA, influence the value of a company. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2015–2017. The samples were manufacturing companies located on the Indonesia Stock Exchange selected using a non-probability sampling method, specifically purposive sampling. Multiple linear regression technique was used for data analysis. Based on the results of the research, the factors that influence the value of the company are disclosure of CSR, GCG, and KA; and they have a positive effect on firm value. Keywords : Corporate Value, CSR, GCG, Foreign Ownership.